Atria-selective antiarrhythmic drugs in need of alliance partners. (July 2019) - Peyronnet, Rémi; Ravens, Ursula
Graphical abstract: Abstract: Atria-selective antiarrhythmic drugs in need of alliance partners. Guideline-based treatment of atrial fibrillation (AF) comprises prevention of thromboembolism and stroke, as well as antiarrhythmic therapy by drugs, electrical rhythm conversion, ablation and surgical procedures. Conventional antiarrhythmic drugs are burdened with unwanted side effects including a propensity of triggering life-threatening ventricular fibrillation. In order to solve this therapeutic dilemma, 'atria-selective' antiarrhythmic drugs have been developed for the treatment of supraventricular arrhythmias. These drugs are designed to aim at atrial targets, taking advantage of differences in atrial and ventricular ion channel expression and function. However it is not clear, whether such drugs are sufficiently antiarrhythmic or whether they are in need of an alliance partner for clinical efficacy. Atria-selective Na + channel blockers display fast dissociation kinetics and high binding affinity to inactivated channels. Compounds targeting atria-selective K + channels include blockers of ultra rapid delayed rectifier (Kv1.5) or acetylcholine-activated inward rectifier K + channels (Kir3.x), inward rectifying K + channels (Kir2.x), Ca 2+ -activated K + channels of small conductance (SK), weakly rectifying two-pore domain K + channels (K2P ), and transient receptor potential channels (TRP). Despite good antiarrhythmic data from in-vitro and animal model experiments, clinical efficacy of atria-selective antiarrhythmic drugs remains to be demonstrated. In the present review we will briefly summarize the novel compounds and their proposed antiarrhythmic action. In addition, we will discuss the evidence for putative improvement of antiarrhythmic efficacy and potency by addressing multiple pathophysiologically relevant targets as possible alliance partners.